New records of avian nasal mites (Mesostigmata: Rhinonyssidae) to Southeastern Brazil - Takatsu, Júlia C.; Bassini-Silva, Ricardo; Spicer, Greg; Hingst-Zaher, Erika; Jacinavicius, Fernando de C. (Entomological Communications, 2021)
The avian nasal mites are a group of Mesostigmata, belonging to the family Rhinonyssidae, Trouessart, 1895, obligate endoparasites of the respiratory system of birds. In Brazil, seven of the eight genera of this family have been recorded. After examining the Acarological Collection of the Instituto Butantan, the species Rallinyssus gallinulae Fain, 1960 and Rhinoecius bisetosus Strandtmann, 1952 were identified from Gallinula galeata (Lichtenstein, 1818) (Gruiformes: Rallidae) and an unidentified owl, respectively. In this study, we are recording for the first time R. gallinulae from Brazil (Rio de Janeiro State), while R. bisetosus is recorded for the second time to this country (São Paulo State), however from a different specific locality.